2011
DOI: 10.1007/s11746-011-1939-0
|View full text |Cite
|
Sign up to set email alerts
|

Odorous Compounds in Bioplastics Derived from Bloodmeal

Abstract: During the processing of bloodmeal-based thermoplastics (BMT), volatile compounds are released which are odorous and unpleasant. Literature searches revealed that blood components are thermally unstable under oxidising conditions and the presence of iron in bloodmeal (BM) may catalyse the formation of various odorous compounds. The objective of this work was to establish an odour profile for BM as well as BMT prior to extrusion and to determine the effect of oxidative treatment on the resulting odour profile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Acetic acid, octanoic acid, and decanoic acid mainly derived from FB, Su and Chien [14] also found those compounds in FB juice and vinegar. Furan compounds were mainly products of linoleic acid oxidation, 2-pentyl-furan has a vegetable-like aroma and earthy aroma, as well as a bean flavor [47]. The compound in samples treated with FB was significantly less than the control due to the addition of antioxidant.…”
Section: Volatile Profilementioning
confidence: 98%
“…Acetic acid, octanoic acid, and decanoic acid mainly derived from FB, Su and Chien [14] also found those compounds in FB juice and vinegar. Furan compounds were mainly products of linoleic acid oxidation, 2-pentyl-furan has a vegetable-like aroma and earthy aroma, as well as a bean flavor [47]. The compound in samples treated with FB was significantly less than the control due to the addition of antioxidant.…”
Section: Volatile Profilementioning
confidence: 98%
“…From Table 3 , it is shown that, at day 0 and 3, higher amounts of 2-pentyl-furan were detected in EEME group. It is reported that many kinds of mushroom contained 2-pentyl-furan which can provide vegetable-like, earthy and bean aroma [ 31 ]. Therefore, the higher levels of 2-pentyl-furan identified in sausages of EEME group could be derived from mushroom extract.…”
Section: Resultsmentioning
confidence: 99%
“…While, at day 7 and 14, the amounts of 2-pentyl-furan in EEME group were lower than control group. As discussed above, this phenomenon can be explained by the lower oxidative reaction occurred in sausages from EEME group, because 2-pentyl furan could be formed from deterioration of lipid and protein at low temperature storage [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solid phase microextraction (SPME) is a rapid, simple, versatile, and solvent‐free extraction technique developed by Pawliszyn and coworkers in 1989 (Verbeek and others ; Liu and others ; Xiao and others ). As an equilibrium method, SPME depends on analyte partitioning between the sample and the fused silica fiber coated with a solid sorbent.…”
Section: Methodsmentioning
confidence: 99%